Vinyl bones. - Backstein, Joseph (Moscow : XL Gallery, 1999)
Vavilov, Nikolai ; Morozova, Elizaveta ; Zapolskaya, Anna ; Kosolapov, Mikhail ; Ilyukhin, Maxim ; Spasolomskaya, Ekaterina ; Dubrovskaya, Oksana ; Korina, Irina ; Struchkova, Natalia ; Loven, Elena ; Magidova, Natalia ; Mariamovskaya, Olga ; Volakhovsky, Alexander ; In the shadow group ; Alimpieva, Olga ; Demina, Karina ; Gorelik, Maxim
Engels & Russisch
Vinyl bones, XL Gallery, Moscow, 17 september 1999, original idea by Oksana Dubrovskaya and Maxim Ilyukhin, curated by Elena Selina
kunstcatalogus